The tert-Amino Effect in Heterocyclic Chemistry. Synthesis of Spiro Heterocycles - D’yachenko, Elisaveta V. (Molecules, 2005)
The tert-amino reaction effect was examined. A new method to synthesize spiro heterocycles is presented. It was shown that the “tert-amino effect” could be applied to the formation of spiro-fused heterocycles. The formation of spiro compounds proceeds in most cases in good yields in a one-pot reaction.